ANALISIS EFISIENSI FAKTOR PRODUKSI USAHA PEMBESARAN BUNGA ANGGREK - Nursinah, Is Zunaini; Rahmanto, Muhammad Ikhwan; Istiqomah, Istiqomah (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2010)
Orchid represent of the decorative very prospective, this matter pursuant to result of analisys of Ditjen Contruct Production Horticulture, orchid reside in on course second after crysan. Analiyst which used in this research to use Function formula pruduce Cobb-Douglas (power function) Y=boX1b1X2b2X3b3X4b4X5b5X6b6eu. Pursuant to result of research indicate that elasticity value produce from labor equel eo -0,004, seed equel to 0,657, charcoal media equel to 0,781, ferny media equel tp 0,985, manure equel to 0,220, and pesticide equel to media,ferry media, pesticide and manure technically have an effect pn positive to result. Production effort magnification of orchid. Result production function anticipation can be written down as flows Y=197,156 X1-0.004X20,657X30,781X40,985X50,220X60,390. Level of media 25,751 manure 111,210, while pesticide equel to 223,846. Usege of production factors, seed charcoal media , ferny media, pesticide and manure not yet efficient while inefficient labor. Scale value effort entrepreneur of orchid reside in area of I (increasing returt scale)